Sleeve gastrectomy decreases high-fat diet induced colonic pro-inflammatory status through the gut microbiota alterations - Cao, Chong; Tan, Xiaozhuo; Yan, Hai; Shen, Qiwei; Hua, Rong; Shao, Yikai; Yao, Qiyuan (Frontiers in Endocrinology, 2023)
Abstract Background: High-fat diet (HFD) induced obesity is characterized with chronic low-grade inflammation in various tissues and organs among which colon is the first to display pro-inflammatory features associated with alterations of the gut microbiota. Sleeve gastrectomy (SG) is currently one of the most effective treatments for obesity. Although studies revealed that SG results in decreased levels of inflammation in multiple tissues such as liver and adipose tissues, the effects of surgery on obesity related pro-inflammatory status in the colon and its relation to the microbial changes remain unknown. Methods: To determine the effects of SG on the colonic pro-inflammatory condition and the gut microbiota, SG was performed on HFD induced obese mice. To probe the causal relationship between alterations of the gut microbiota and improvements of pro-inflammatory status in the colon following SG, we applied a broad-spectrum antibiotics cocktail on mice that received SG to deplete the gut microbial changes. The pro-inflammatory shifts in the colon were assessed based on morphology, macrophage infiltration and expressions of a variety of cytokine genes and tight junction protein genes. The gut microbiota alterations were analyzed using 16s RNA sequencing. RNA sequencing of colon was conducted to further explore the role of the gut microbiota in the amelioration of pro-inflammation in the colon following SG at a transcriptional level. Results: Although SG did not lead to pronounced changes of colonic morphology and macrophage infiltration in the colon, there were significant decreases in the expressions of several pro-inflammatory cytokines including IL-1β, IL-6, IL-18 and IL-23 as well as increased expressions of some tight junction proteins in the colon following SG, suggesting an improvement of pro-inflammatory status. This was accompanied by changing populations of the gut microbiota such as increased richness of Lactobacillus subspecies following SG. Importantly, oral administrations of broad-spectrum antibiotics to deplete the intestinal bacteria abrogated surgical effects to relieve colonic pro-inflammation. This was further confirmed by transcriptional analysis of colon indicating that SG regulated inflammation related pathways in a manner that was gut microbiota relevant.